Reducing the gap in perceptions of legitimacy of victims and non-victims: The importance of police performance. (May 2016) - Aviv, Gali; Weisburd, David
Crime victims are a unique subgroup who evaluate the police and police legitimacy more harshly than those who have not been victimized. This could be explained by their victimization, and their special needs from and expectations of the police. Due to the importance of crime victims for the criminal justice system, the current study examines the mechanisms underlying differences in legitimacy evaluations of victims and non-victims. We focus on the two main antecedents of legitimacy: procedural justice and police performance. We find that procedural justice operates similarly for victims and non-victims, but that police performance plays a much more important role as an antecedent for victims. These findings suggest that managing perceptions of police performance may be key to closing the gap in legitimacy evaluations between victims and non-victims.